PEMOTIVASI KNOWLEDGE SHARING MANAJERIAL MELALUI MEDIA INTERNET - Mujilan, Mujilan; Purbandari, Theresia (Widya Warta, 2015)
This study identifies the factors that influence knowledge sharing via internet. The factors are categorized into internal motivation, external motivation, and sharing barriers. It is motivations and barriers that influence the intention of sharing through knowledge sharing attitudes. The data were collected by surveying the lecturers of S-1 Program of Accounting Department in East Java. Hypothesis testing made use of SmartPLS Graph software version 2.0. The results proved that there were factors that significantly influence the attitudes, namely perceived enjoyment in helping others as internal motivation, perceived affiliation as external motivator, and perceived loss of knowledge power as barriers for sharing. The direction of influence for the motivating factor in attitudes was positive and that for the barrier factor was negative. Attitudes had a strong positive influence on the intention of knowledge sharing. But, there was no significant influence of information technology facilities and information technology support on the attitudes of knowledge sharing. This means that there were characteristics of knowledge sharing in the context of managerial information in the lecturers of S-1 Program of Accounting Department. Some non-significant motivating variables indicated that there were unique characteristics of the respondents which might be different from those of other respondents.